The characterisation of polydimethylsiloxane containing gold nanoparticles as a function of curing time. (12th April 2021) - Cutroneo, Mariapompesa; Havranek, Vladimír; Mackova, Anna; Malinsky, Petr; Torrisi, Alfio; Silipigni, Letteria; Slepicka, Petr; Fajstavr, Dominik; Torrisi, Lorenzo
Abstract : Spherical gold nanoparticles (NPs), 10 nm in diameter, have been dispersed in a type of polydimethylsiloxane, whose polymerisation requires accurate temperature control. At the temperature of 100°C, the polymerisation of the polydimethylsiloxane matrix is completed in 15 min, whereas at room temperature (∼20°C), it takes about 24–48 h. Gold NPs were incorporated into polydimethylsiloxane after which the resulting nanocomposites were placed in an oven preheated to 100°C for different curing times. Both porous and bulk nanocomposites were obtained using a bottom‐up approach. Polydimethylsiloxane (PDMS) nanocomposites with the weight‐percentage concentration of 0.2% of Au NPs were cured for 15, 30 and 45 min. Different curing times have affected the Au‐NP properties. The network of porous PDMS nanocomposite promotes a uniform anchoring of the gold NPs. The porous PDMS nanocomposite samples, prepared using the sugar‐template method, have been compared with the bulk counterpart to obtain a full characterisation of the material. The dependence of the morphological and electrical properties of gold NPs on their size has been studied by atomic‐force microscopy and two‐point‐probe electrical‐conductivity measurement. The optical performance of the bulk PDMS nanocomposites has been analysed by ultraviolet–visible (UV–vis) spectroscopy in the transmission mode. An enhancement of the absorption was observed after the increase of both the nanocomposite‐curing time and the percentage of the Au NPs used as fillers. The fabricated nanocomposite can be used to manufacture optical‐sensing devices, switches in optoelectronics and optical waveguides.